2014
DOI: 10.1186/preaccept-6871346891381394
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors, demographics and medications associated with depression risk in an international sample of people with multiple sclerosis

Abstract: Background: Depression is the most common co-morbidity for people with Multiple Sclerosis (MS); irrespective of disease severity, depression has the greatest impact on quality of life. An emerging paradigm in the treatment of depression is lifestyle medicine. There is significant potential to prevent and treat depression through modification of lifestyle risk factors for people with MS. This study sought to understand the association between lifestyle risk factors, medication and depression risk through the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 48 publications
8
23
0
Order By: Relevance
“…Observational studies in people with MS have consistently shown an association between physical inactivity and depression as well as excessive alcohol use and depression, so our results here are in keeping with these prior findings. We did not find an association between BMI and depression prevalence or severity, however, which is inconsistent with previous studies . This could reflect differences in study design or populations; however, this is mere speculation and more research is needed to clarify this.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Observational studies in people with MS have consistently shown an association between physical inactivity and depression as well as excessive alcohol use and depression, so our results here are in keeping with these prior findings. We did not find an association between BMI and depression prevalence or severity, however, which is inconsistent with previous studies . This could reflect differences in study design or populations; however, this is mere speculation and more research is needed to clarify this.…”
Section: Discussionsupporting
confidence: 89%
“…Every unit increase in SNAP score was associated with a 17% reduction in prevalent depression and a 0.44 unit lower actual HADS‐depression score. The findings are in line with previous work showing that smoking and poor diet were associated with increased risk of depression in people with MS . Research into the mechanisms between diet and mood is still emerging, but evidence for this association is strong within the general population .…”
Section: Discussionmentioning
confidence: 99%
“…There is no strong evidence to link Vitamin D insufficiency with HPA-axis dysregulation. However, Vitamin D remains a worthy candidate for further investigation as a therapeutic option for PD due to the strong evidence that Vitamin D metabolism exerts a significant influence over the progression of other neurological conditions such as multiple sclerosis ( 314 ) and supplementation with omega-3 fatty acids significantly reduces the risk of depression ( 315 ).…”
Section: Depression In Parkinson’s Diseasementioning
confidence: 99%
“…3,8 People with MS have many stressors due to their disease. Psychological problems such as denial of disease, depression, anxiety, and negative changes in lifestyle and decreased social interactions affect up to 80% of people with MS. 9,10 Moreover, symptoms such as pain, blurred vision, fatigue, dizziness, physical imbalance, and urologic and sexual dysfunctions negatively affect health-related quality of life in these patients. 11 Therefore, coping with such problems may be a key to the management of MS and its associated symptoms.…”
Section: The Jcsmentioning
confidence: 99%